Prototype development and demonstration of unified management-control system of access-type OTN - Ruiquan JING; Guoyong ZHAO; Yunbin XU; Xiaoli HUO (Dianxin kexue)
The decoupling of client-side OTN and network-side OTN equipment is a prerequisite for improving OTN networking flexibility and reducing the cost.Based on the concept of the management-control continuum (MCC),a unified management-control system architecture for access-type OTN equipment was proposed,including the management-control interface and GCC interoperability specification,and auto-discovery process.A unified management-control system (UMS) of the access-type OTN equipment was developed to realize the unified management and control of multi-vendor equipments.